The "Tender Technicians" of Nielsen Norman Group Videos - Jaci Wilkinson (Weave: Journal of Library User Experience)
Nielsen Norman Group (NN/g) YouTube content predominantly features young, white or white-presenting, normatively attractive women. The uniform presentation of these women, combined with the unspecific, universalizing script content, compromises their expertise and is objectifying. This treatment, combined with a lack of diversity in featured employees, undercuts NN/g’s standing as an authoritative resource in the field of user experience (UX). Additionally, it contributes to a sexist representation of UX as a pink-collar field and compounds librarianship’s own pink-collar culture and whiteness problems. NN/g video content echoes a century-old manipulation of librarians as “tender technicians” (Garrison, 1972; Sloniowski, 2016), now made into clickbait using the aesthetics of YouTube beauty vloggers.